The Influence of Submission Devices on User-Generated Content—A Systematic Literature Review and Meta-Analysis - Wolf, Lukas; Madlberger, Maria (International Journal of Consumer Studies, 2025)
In today's ever-changing and modern world, user-generated content (UGC) on the internet exerts a significant influence on consumers. Therefore, understanding UGC and its design is of great interest to researchers and practitioners alike. One examined factor influencing UGC is the submission device, such as the smartphone, tablet, or laptop. Despite digital devices offering similar capabilities for content creation and submission, they differ substantially in their characteristics, including screen size, user interface, and usage context. This study conducts a framework-based systematic literature review on the influence of submission devices on UGC. Through a comprehensive descriptive analysis, the authors examine the theories, contexts, and methods used, offering a structured overview of current research. In a subsequent weight analysis and meta-analysis, the strength and combined effect sizes of the relationships studied are illustrated and an insight into moderators that explain result variations is provided. The findings reveal that the choice of submission device (mobile vs. nonmobile) exerts a multi-faceted influence on the creation of UGC. Mobile devices, as opposed to nonmobile devices, demonstrate a significant and moderate negative impact on temporal distance, text length, and diversity of UGC across studies. This analysis clarifies previous inconsistencies and establishes the robustness of specific relationships, providing practical recommendations for managers to adapt marketing strategies for different digital device